2016
DOI: 10.4236/wjcd.2016.67023
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Cardiovascular Diseases in the Congo-Brazzaville Pygmies

Abstract: Objective: To evaluate the prevalence and determinants of overall cardiovascular risk among the pygmies of Congo Brazzaville. Methods: Cross-analysis of anthropometric data, clinical and laboratory 273 indigenous subjects including 54 patients with cardiovascular disease (CVD) and 183 without CVD, aged 29 to 69 years. The cardiovascular risk stratification table WHO/ISH 2003 was used to assess overall cardiovascular risk level. Multiple logistic regression was used to assess the independent determinants of car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
(21 reference statements)
1
3
0
Order By: Relevance
“…The severity of CAD is directly proportional to the number of components. 24 In the present study, it was seen that all 5 components of MetS were more frequently in ACS patients with the MetS as compared to without MetS, which is statistically significant (p<0.05). This was in congruence with study findings by Ranjith et al 25 MetS increases cardiovascular risk and each of its components is associated with an increased risk of CVS.…”
Section: Discussionsupporting
confidence: 60%
“…The severity of CAD is directly proportional to the number of components. 24 In the present study, it was seen that all 5 components of MetS were more frequently in ACS patients with the MetS as compared to without MetS, which is statistically significant (p<0.05). This was in congruence with study findings by Ranjith et al 25 MetS increases cardiovascular risk and each of its components is associated with an increased risk of CVS.…”
Section: Discussionsupporting
confidence: 60%
“…Although after adjusting of sex, there was no statistically significant relationship between the categories of age and physical activity with the MetS in the CAD patients; however, these variables were significantly higher among CAD patients with MetS than in those without MetS. Similar studies in Iranian adult population reported that all major components of MetS increase with aging [ 19 , 35 , 36 ], and a higher rate of MetS [ 7 , 8 , 19 ] and its components [ 21 ] has been reported in women compared with men in earlier studies. Karimi et al [ 29 ] demonstrated that the patients with CAD were more male with older age.…”
Section: Discussionmentioning
confidence: 83%
“…The abdominal obesity, dyslipidemia (high TG and low HDL-C) [ 1 , 2 , 21 ], hypertension [ 2 ] and hyperglycemia [ 2 , 21 ] most often were reported as the MS components, and the severity of CAD increased with the number of components [ 2 ]. A study performed in Shanghai showed that among individual components of MetS, low HDL, high FBG, and high BP had the highest OR for coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation